2010
DOI: 10.1107/s1600536810039012
|View full text |Cite
|
Sign up to set email alerts
|

5,7-Dihydroxy-3,6-dimethoxy-2-(4-methoxyphenyl)-4H-chromen-4-one monohydrate

Abstract: The title compound, C18H16O7·H2O, is a flavonoid isolated from Dodonaea viscosa­. The benzopyran ring system of the flavonoid is essentially planar [maximum deviation = 0.025 (2) Å] and inclined at 5.83 (2)° to the attached benzene ring. The water of hydration is involved in extensive hydrogen bonding, assembling the mol­ecules into a supra­molecular network via classical inter­molecular O—H⋯O hydrogen bonding. The crystal structure is further stabilized by π–π stacking inter­actions [centroid–centroid distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…A search of the Cambridge Structural Database (Groom et al, 2016) revealed the structure of a related compound, 5,7dihydroxy-3,6-dimethoxy-2-(4-methoxyphenyl)-4H-chromen-4-one monohydrate (Mohammad et al, 2010), in which the 4-hydroxyl group of chrysin is replaced by a 3-bromopropyne group.…”
Section: Structure Descriptionmentioning
confidence: 99%
“…A search of the Cambridge Structural Database (Groom et al, 2016) revealed the structure of a related compound, 5,7dihydroxy-3,6-dimethoxy-2-(4-methoxyphenyl)-4H-chromen-4-one monohydrate (Mohammad et al, 2010), in which the 4-hydroxyl group of chrysin is replaced by a 3-bromopropyne group.…”
Section: Structure Descriptionmentioning
confidence: 99%